Análisis del sistema de personajes femeninos en la novela Baldomera de Alfredo Pareja Diezcanseco - Guevara Roldan, Sonia Patricia (2023)
The purpose of this research is to analyse the system of female characters in the novel "Baldomera" by Alfredo Pareja Diezcanseco. For this study of female protagonists, a stylistic and structural analysis was carried out, and finally, semiotics was used to search for important aspects of women in Alfredo Pareja Diezcanseco's work, such as values, where Austin's theory of speech acts was applied. Within the methodology for the execution of the work, underlining has been used, especially where the female figure is found; then placed within two analysis matrices, one for the selection of the interpreters and the other for the application of Austin's theory using the locutionary, illocutionary and perlocutionary acts given in this practice; Each of these studies helps us to identify the way in which women are valued within the work, as well as in that era, on the other hand, the importance of women in Ecuadorian society was emphasized and how they have not been taken as an indispensable entity in the life of families and in society.